2019
DOI: 10.17221/80/2019-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a poly(lactic-acid) scaffold filled with poly(lactide-co-glycolide)/hydroxyapatite nanofibres for reconstruction of a segmental bone defect in a canine model

Abstract: Critical-sized bone defects are a difficult problem in both human and veterinary medicine. To address this issue, synthetic graft materials have been garnering attention. Abundant in vitro studies have proven the possibilities of poly(lactic-acid) (PLA) scaffolds and poly(lactide-co-glycolide)/hydroxyapatite (PLGA/HAp) nanofibres for treating bone defects. The present study aimed at conducting an in vivo assessment of the biological performance of a three dimensional (3D)-printed PLA scaffold filled with a PLG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…After creating a 20 mm-long defect in the radius bone, the 3D scaffold was replaced and subsequently fixed with an LC-DCP plate. The results indicated the biodegradability of the scaffold and its replacement by new bone tissue [69]. Three-dimensional-printed PCL/β-TCP scaffold was used in a bone defect resulting of limb-sparing surgery in a dog with distal radial OSA.…”
Section: Customized Scaffoldsmentioning
confidence: 98%
See 3 more Smart Citations
“…After creating a 20 mm-long defect in the radius bone, the 3D scaffold was replaced and subsequently fixed with an LC-DCP plate. The results indicated the biodegradability of the scaffold and its replacement by new bone tissue [69]. Three-dimensional-printed PCL/β-TCP scaffold was used in a bone defect resulting of limb-sparing surgery in a dog with distal radial OSA.…”
Section: Customized Scaffoldsmentioning
confidence: 98%
“…Three-dimensional-printed implants can also be designed with scaffold structure which can enhance osteointegration. In veterinary clinical models, scaffold structures have been used as lower extremity implants as well as in limb-sparing surgeries, tibial tuberosity advancement (TTA), and the reconstruction of critical-sized bone defects [4,8,10,14,69]. Critical-sized bone defects are difficult to treat; in cases where allograft bone is unavailable for the required dimension of the defect, 3D-printed scaffolds may be considered.…”
Section: Customized Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, BMP-2 is the most powerful osteoplastic facilitator and is characterized by play-ing an important role in many stages of the osteoplastic process. However, results are reported that excessive concentration of BMP promotes cell death and hinders bone formation (3,4,27).…”
Section: Discussionmentioning
confidence: 99%